Positron Emission Tomography-Guided Bone Marrow-Sparing Radiation Therapy for Locoregionally Advanced Cervix Cancer: Final Results From the INTERTECC Phase II/III Trial - Williamson, Casey W; Sirák, Igor; Xu, Ronghui; Portelance, Lorraine; Wei, Lichun; Tarnawski, Rafal; Mahantshetty, Umesh; Heide, Elena S; Yashar, Catheryn M; McHale, Michael T; Bosch, Walter; Lowenstein, Jessica; et al. (International journal of radiation oncology, biology, physics, 2022)
PURPOSE: To test effects of positron emission tomography (PET)-based bone marrow-sparing (BMS) image-guided intensity modulated radiation therapy (IG-IMRT) on efficacy and toxicity for patients with locoregionally advanced cervical cancer. METHODS AND MATERIALS: In an international phase II/III trial, patients with stage IB-IVA cervical carcinoma were treated with either PET-based BMS-IG-IMRT (PET-BMS-IMRT group) or standard image-guided IMRT (IMRT group), with concurrent cisplatin (40 mg/m2 weekly), followed by brachytherapy. The phase II component nonrandomly assigned patients to PET-BMS-IMRT or standard IMRT. The phase III trial randomized patients to PET-BMS-IMRT versus IMRT, with a primary endpoint of progression-free survival (PFS) but was closed early for futility. Phase III patients were analyzed separately and in combination with phase II patients, comparing acute hematologic toxicity, cisplatin delivery, PFS, overall survival (OS), and patterns of failure. In a post-hoc exploratory analysis, we investigated the association between pretreatment absolute lymphocyte count (ALC) and OS. RESULTS: In total, 101 patients were enrolled on the phase II/III trial, including 29 enrolled in phase III (PET-BMS-IMRT group: 16; IMRT group: 13) before early closure. Median follow-up was 33 months for phase III patients and 39 months for all patients. PFS and OS at 5 years for all patients were 73.6% (95% confidence interval [CI], 64.9%-84.3%) and 84% (95% CI, 76%-92.9%]), respectively. There were no differences in number of cisplatin cycles, OS, PFS, or patterns of failure between groups for the combined cohort. The incidence of acute grade ≥ 3 neutropenia was significantly lower in the PET-BMS-IMRT group compared with IMRT for randomized patients (19% vs 54%, χ2P = .048) and in the combined cohort (13% vs 35%, χ2P = .01). Patients with pretreatment ALC ≤ 1.5 k/µL had nonsignificantly worse OS on multivariable analysis (HR 2.85; 95% CI, 0.94-8.62; adjusted P = .216), compared with patients with ALC > 1.5 k/µL. There was no difference in posttreatment ALC by treatment group. CONCLUSIONS: PET-BMS-IMRT significantly reduced acute grade ≥3 neutropenia, but not treatment-related lymphopenia, compared with standard IMRT. We found no evidence that PET-BMS-IMRT affected chemotherapy delivery or long-term outcomes, and weak evidence of an association between pretreatment ALC and OS.
Keywords: Uterine Cervical Neoplasms; výsledek terapie; nádory děložního čípku; kostní dřeň; Radiotherapy, Image-Guided; Radiotherapy, Intensity-Modulated; Treatment Outcome; Positron-Emission Tomography; cisplatina; pozitronová emisní tomografie; radioterapie s modulovanou intenzitou; radioterapie řízená obrazem; lidé; Female; ženské pohlaví; Cisplatin; Humans; Bone Marrow